Pengaruh Penerapan Strategi Pembelajaran Kooperatif Learning Tipe Numberred Heads Together (NHT) terhadap Motivasi Belajar Siswa PAI SMAN 1 Kinali Kabupaten Pasaman Barat - Anwar, Riza Rizkiah; Supriadi, Supriadi; Arsya, Fajriyani (ALSYS, 2023)
This research is motivated by the lack of student motivation to participate in PAI learning activities because teachers have not used interesting strategies when learning takes place. So one of the efforts that must be made so that students are motivated to take part in PAi learning is with the help of the Numberred Heads Together (NHT) learning strategy. The formulation of the problem in this research is how much influence the application of the Numberred Heads Together (NHT) type cooperative learning strategy in PAI subjects, the material of pursuing glory through life, has on student learning motivation. This research aims to determine the effect of the Numberred Heads Together (NHT) learning strategy on student learning motivation. The method used in this research is a quantitative type of quasi experiment. The population in this study was all class X at SMAN 1 Kinaii. The sampling in this study was random sampling, namely classes E1 and E2 as the research sample. The research results showed that the questionnaire was calculated using the SPSS test. With a sig result < α, namely 0.000 <0.005, it can be concluded that Ho is rejected and Ha is accepted. So it can be concluded that student learning motivation in PAI subjects is influenced by using the Numberred Heads Together (NHT) learning strategy which is used when learning takes place at SMAN 1 Kinali.